Analysis Of Basic Materials Sector Financial Performance During And After The Covid-19 Pandemic In Readiness For ESG Adoption - Gunawan, Cornelia Lisia; Jakaria, Jakaria; Ristaviasha, Clarisya; Fang, Hellen Fang; Junitha, Katherine; Wiguno, Theola Darius; Maringka, Tracy Rachel; Neyrine, Varlonia (Jurnal Fokus Manajemen, 2025)
This research examines and analyzes the readiness of companies in the basic materials sector to implement Environmental, Social, and Governance (ESG) principles by analyzing fluctuations in financial ratios before and after the COVID-19 pandemic. Using a quantitative approach through normality testing, the Wilcoxon Signed Rank Test, and Paired-Samples T-Test, supported by qualitative analysis, the results show that most liquidity and solvency ratios improved, while profitability remained stagnant and activity ratios declined significantly. These findings indicate that a company’s financial condition can serve as an early indicator of ESG readiness. Firms with strong financial stability are more likely to consistently fund and implement sustainability initiatives. The study also recommends integrating financial analysis with non-financial data to provide a more comprehensive view of a company’s sustainability performance.